The Impact of Undergraduate Tutor System in Chinese 8-Year Medical Students in Scientific Research - Liao, Yuxuan; Zhou, Hu; Wang, Fang; Zhao, Mingyi; Wu, Jianzhen; Rong, Pengfei (Frontiers in Medicine, 2022)
Purpose: To evaluate the effect and influence of the undergraduate tutor system on the undergraduate stage of Chinese eight-year medical program students in scientific research. Methods: We collected related data from 194 medical students in Xiangya Medical School of Central South University. The questionnaire was composed of three parts including eight questions for basic information about individual and undergraduate tutor system, five questions for the subjective impact of the undergraduate tutor system, and twenty-two questions for accessing the scientific research ability and academic results. The students were mainly divided into three groups to compare different kinds of undergraduate tutor systems, including single tutor for multiple students’ system (Group A), multiple tutors for multiple students’ system (Group B), and no tutor system for comparison (Group C). Results: The type of tutorial system, the frequency of guidance, and the way of guidance were independent influence factors of the view of eight-year medical students on scientific research. Group B behaved better than group C in literature processing (P=0.012), experimental operation (P<0.001), statistical analysis (P<0.001), and manuscript producing (P=0.019). Group A and B joined in more National college students' innovation and entrepreneurship training programs (P=0.003, P<0.001). The most popular types of articles published by students were bioinformatic, Meta-analysis, and reviews. Conclusions: Undergraduate tutor system has made tremendous achievements in cultivating students’ scientific research capacity. The system of multiple tutors for multiple students seems to be the better form, however, implement improvement should be considered to better educate students.